Pendampingan Akuntansi Dalam Menentukan Harga dan Pengelolaan Persediaan Untuk Memajukan Usaha Masyarakat Desa Bangbang, Bangli - Desak Rurik Pradnya Paramitha Nida; I Gusti Agung Prama Yoga; I Nyoman Angga Prabawa (Postgraduated Community Service Journal, 2024)
Financial statements play an important role in providing information for making business decisions or policies. Financial statements are the end result of the accounting process. However, there are still many stigmas in society that consider accounting to be difficult. In fact, if done consistently and orderly, the information obtained will greatly impact the sustainability of the business both as a source of information and a control tool. The most basic thing, in basic accounting that needs to be understood is the process of how financial statements are made. Starting from collecting transaction evidence, grouping, recording, analyzing and presenting accounting information. The first stage is collecting evidence. This initial stage is still widely ignored in recording. Even though transaction evidence is needed to prove the validity of transaction occurrences and measurements in transaction recognition. In collaboration with the Bangbang Village BUPDA, the service team conducted assistance involving the Tembuku Bangbang Bali Village community, namely traders, BUPDA (Baga Utsaha Padruwen Desa Adat) administrators and local LPD (Village Credit Institution) administrators in early June 2024 to get assistance and training on the role of accounting in advancing business, basic accounting, inventory methods, how to make transaction evidence by utilizing technology. The methods used were socialization and discussion groups. The obstacle so far that has been felt is the difficulty of compiling reports due to forgetting or not taking notes. Not everything is "well recorded" because they still use manual records. Shopkeepers do double duty serving customers, as well as cashiers and record keepers. So very often experience constraints lack of time to record, so there are some transactions that are missed recorded. This affects the relevance of transaction data. The service team helps provide assistance as well as tools and systems used to facilitate the creation of simple proof of transactions and cash flow using technology. So there is no need to write per-item transactions manually, but using software, inputting transactions, then printing notes automatically using a thermal printer. At the end of the period, you can draw a summary of transactions in the form of cash flow. It is hoped that this PKM can have a positive impact on the progress of the Village, especially the traders, the community and BUPDA. With the records of transactions, MSME players or organizations can get economic information related to business.